Serotonin modifies cytoskeleton and brush-border membrane architecture in human intestinal epithelial cells - Gill, Ravinder K. (American Physiological Society, 2008)
Serotonin or 5-hydroxytryptamine (5-HT) influences numerous functions in the gastrointestinal tract. We previously demonstrated that 5-HT treatment of Caco-2 cells inhibited Na(+)/H(+) exchangers (NHE) and Cl(−)/OH(−) exchange activities via distinct signaling mechanisms. Since regulation of several ion transporters such as NHE3 is influenced by intact cytoskeleton, we hypothesized that 5-HT modifies actin cytoskeleton and/or brush-border membrane architecture via involvement of signaling pathways. Ultrastructural analysis showed that 5-HT (0.1 μM, 1 h) treatment of Caco-2 cells caused the apical membrane to assume a convex dome shape that was associated with shortening of microvilli. To examine whether these cellular architecture changes are cytoskeleton driven, we analyzed actin cytoskeleton by fluorescence microscopy. 5-HT induced basal stress fibers with prominent cortical actin filaments via 5-HT3 and 5-HT4 receptor subtypes. This induction was partially attenuated by chelation of intracellular Ca(2+) and PKCα inhibition (Go6976). In vitro assays revealed that PKCα interacted with actin and this association was increased by 5-HT. Our data provide novel evidence that 5-HT-induced signaling via 5-HT3/4 receptor subtypes to cause Ca(2+) and PKCα-dependent regulation of actin cytoskeleton may play an important role in modulation of ion transporters that contribute to pathophysiology of diarrheal conditions associated with elevated levels of 5-HT.